Development of the Whistleblowing Likelihood Index (WLI) for occupational fraud mitigation: A preliminary study - Roslan, Muhammad Syahmi Adli; Hamid, Muhammad Hariz; Said, Roshima (International Journal of Accounting, Finance and Business, 2025)
Occupational fraud, characterised by the misuse of organisational roles for personal benefit, poses significant risks across industries, resulting in major financial losses, reputational harm, and diminished stakeholder trust. It highlights the need for improved detection and prevention methods. This study examines whistleblowing as an essential mechanism for fraud detection, identifying it as a critical approach for revealing unethical practices that often evade traditional audits and compliance procedures. A review of the literature reveals that the likelihood of whistleblowing is influenced by a combination of organisational, individual, situational, and demographic factors, each shaping employees' decisions to report misconduct. Yet, current fraud assessment models frequently overlook these behavioural and contextual aspects, limiting their effectiveness in supporting a whistleblowing culture. To bridge this gap, the study develops the Whistleblowing Likelihood Index (WLI), a structured tool designed to evaluate whistleblowing propensity within diverse organisational settings by quantifying the key influencing factors. By fostering a supportive climate for whistleblowing, organisations can strengthen defences against occupational fraud, bolster trust, and align with regulatory standards. The WLI offers a practical approach for reinforcing fraud prevention efforts and supports the broader aim of cultivating integrity-driven organisational cultures.